2022
DOI: 10.1002/jwmg.22246
|View full text |Cite
|
Sign up to set email alerts
|

Golden eagle use of winter roadkill and response to vehicles in the western United States

Abstract: Vehicle collisions are a significant source of wildlife mortality worldwide, but less attention has been given to secondary mortality of roadkill scavengers, such as the golden eagle (Aquila chrysaetos). We sought to quantify golden eagle winter use of roadkill mammal carcasses and eagle flushing from vehicles in Oregon, Utah, and Wyoming, USA, as proxies for strike risk, using motion-sensitive cameras. We monitored 160 carcasses and captured 2,146 eagle-vehicle interactions at 58 carcasses (1-240 observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…We focused our model improvements on updating the representation of golden eagle behavior at carcasses. The HWI data consisted of 1,933 photo interpretations of eagle behavior at roadside deer carcasses, captured with motion-sensitive cameras (see Slater et al [2022] for details). The interpretations were from a larger set of camera trap observations, and we omitted 12 interpretations due to evident transcription errors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We focused our model improvements on updating the representation of golden eagle behavior at carcasses. The HWI data consisted of 1,933 photo interpretations of eagle behavior at roadside deer carcasses, captured with motion-sensitive cameras (see Slater et al [2022] for details). The interpretations were from a larger set of camera trap observations, and we omitted 12 interpretations due to evident transcription errors.…”
Section: Methodsmentioning
confidence: 99%
“…Given recent empirical findings and the results of our updated modeling, carcass removal should be added as an acceptable mitigation option. While the mitigation is called “removal”, the carcasses simply need to be moved away from the roadsides; HWI found that moving carcasses twelve meters from the road allows eagles to continue to scavenge and reduces collision risk (Slater et al 2022). The data required to determine credit - traffic volume, expected “hot-spots” of roadkill and eagle density estimates - are widely available beyond the example we used in Wyoming.…”
Section: Management Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hereafter, carcass relocation refers to moving a carcass ≥12 m away from the roadside, following Slater et al (2022). While factors could constrain the ability to move the carcass safely, such as property boundaries, topography, or fencing, Slater et al (2022) reported that 2 people could easily and quickly move a carcass with rope and a sled under any conditions. We integrated the updated model with the REA to translate the model output into mitigation credit.…”
mentioning
confidence: 99%